Development of emergent processes and threshold of consciousness with levels of processing - Watanabe, Ryoichi; Moriguchi, Yusuke (Frontiers in Psychology, 2024)
Introduction: The transition of experience from unconscious to conscious, the emergent process, is a crucial topic in consciousness studies. Three frameworks exist to explain the process: 1) consciousness arises in an all-or-none manner; 2) consciousness arises gradually; 3) consciousness arises either all at once or gradually, depending on the level of stimulus processing (low- vs. high-level). However, the development of emergent processes of consciousness remains unclear. This study examines the development of emergent processes of consciousness based on the level of stimulus processing framework. Methods: Ninety-nine children (5–12-year-olds) and adults participated in two online discrimination tasks. These tasks involved color discrimination as lower-level processing and number magnitude discrimination as higher-level processing, as well as backward masking with stimulus onset asynchronies (SOAs) varying from 16.7 to 266.7 ms. We measured objective discrimination accuracy and used a 4-scale Perceptual Awareness Scale (PAS) to assess subjective awareness. We fit the data to a four-parameter nonlinear function to estimate the center of the slope (threshold) and the range of the slope (gradualness, the measure of emergent process of consciousness) of the model. Results: The results showed the threshold of objective discrimination was significantly higher in 5–6-year-olds than in 7–12-year-olds, but not of subjective awareness. The emergent process of objective discrimination in the number task was more gradual than in the color task. Discussion: The findings suggest that the thresholds of subjective awareness in 5-6-year-olds and objective discrimination in 7-9-year-olds are similar to those in adults. Moreover, the emergent processes of subjective awareness and objective discrimination in 5-6-year-olds are also similar to those in adults. Our results support the Level of Processing hypothesis but suggest that its effects may differ across developmental stages.